Polinizadores do maracujá-amarelo (Passiflora edulis f. flavicarpa Deneger, Passifloraceae) no Triângulo Mineiro: riqueza de espécies, freqüência de visitas e a conservação de áreas naturais - Yamamoto, Marcela (2009)
The evidence of native pollinators population decrease worldwide has led to conservation initiatives and promoted several projects, including in Brazil, aiming to better understand pollinators and recommend management and conservation strategies. In this sense, yellow passion fruit crop seems to represent an interesting model to be studied, considering its dependence on pollination services for fruit production. Their effective pollinators are solitary and large native carpenter bees, which nest in dead wood. Also, this crop is important for sustainable development in the Triângulo Mineiro region, one of the most human disturbed areas in Cerrado. The thesis general objective was to verify the relationship between natural areas conservation around the yellow passion fruit orchards and the pollination services of this crop in Triângulo Mineiro region. For this, we estimate the richness of yellow passion fruit native pollinators, as well as to know their behavior on orchards and frequency of visits. It aimed also to associate that information with passion-fruit pollination service in a Brazil Central region. Moreover, we made a preliminary analysis of the effects of natural areas land cover around orchards on the crop pollination and productivity. Data were collected during flowering seasons from 2004 to 2008, on yellow passion fruit commercial orchards at Uberlândia and Araguari municipalities, Minas Gerais State. The species richness of pollinator and natural fruit-set were higher than found in other areas of Brazil. The yellow passion fruit natural fructification was explained by pollinator species richness, but was not explained neither by frequency nor by visitation rates of pollinators. Floral visitors were recorded during along the afternoon while there were open flowers, although they were missing in some months of flowering seasons. The Xylocopa spp population was estimated in 150-210 individuals and this value appeared to be enough to pollinate a 0.5ha yellow passion fruit orchard, maintaining 38.7% of natural fruit-set. In some areas, Apis mellifera bee was damaging to passion-fruit production by quickly reducing available pollen to pollination service. Results indicated pollen limitation to this crop, probably caused by the low frequency of pollinators. Hand pollination was more effective on fruit formation, but had an additional cost to the producers. The pollinator species richness semmed to be associated with degree of natural areas conservation around the orchards, although the proportion of these natural areas alone did not show a significant relation with pollinator richness and crop visitation rates on studied areas. Other information, such as management practices, distance and quality of cerrado natural areas remnants and even ruderal plants around the orchards are important to maintain the pollinators resources availability and description of yellow passion fruit system in all geographical context constituting suitable arguments to be used in order to justify conservation policies.